Cognitive impairment, the central vein sign, and paramagnetic rim lesions in RIS. (December 2021) - Oh, Jiwon; Suthiphosuwan, Suradech; Sati, Pascal; Absinta, Martina; Dewey, Blake; Guenette, Melanie; Selchen, Daniel; Bharatha, Aditya; Donaldson, Emily; Reich, Daniel S; Feinstein, Anthony
Objective: The central vein sign (CVS) and "paramagnetic rim lesions" (PRL) are emerging imaging biomarkers in multiple sclerosis (MS) reflecting perivenular demyelination and chronic, smoldering inflammation. The objective of this study was to assess relationships between cognitive impairment (CI) and the CVS and PRL in radiologically isolated syndrome (RIS). Methods: Twenty-seven adults with RIS underwent 3.0 T MRI of the brain and cervical spinal cord (SC) and cognitive assessment using the minimal assessment of cognitive function in MS battery. The CVS and PRL were assessed in white-matter lesions (WMLs) on T2*-weighted segmented echo-planar magnitude and phase images. Multivariable linear regression evaluated relationships between CI and MRI measures. Results: Global CI was present in 9 (33%) participants with processing speed and visual memory most frequently affected. Most participants (93%) had ⩾ 40% CVS + WML (a threshold distinguishing MS from other WM disorders); 63% demonstrated PRL. Linear regression revealed that CVS + WML predicted performance on verbal memory( β  =-0.024, p  = 0.03) while PRL predicted performance on verbal memory ( β  = -0.040, p  = 0.04) and processing speed ( β  = -0.039, p  = 0.03). Conclusions: CI is common in RIS and is associated with markers of perivenular demyelination and chronic inflammation in WML, such as CVS + WML and PRL. A prospective follow-up of this cohort will ascertain the importance of CI, CVS, and PRL as risk factors for conversion from RIS to MS.